Evaluation of the Transport and Binding of Dopamine-Loaded PLGA Nanoparticles for the Treatment of Parkinson's Disease Using In Vitro Model Systems - Karin Danz; Jana Fleddermann; Marcus Koch; Elena Fecioru; Lorenz Maahs; Nicole Kinsinger; Johannes Krämer; Annette Kraegeloh; Sylvia Wagner (MDPI AG, 2024)
The treatment of Parkinson's disease has been moving into the focus of pharmaceutical development. Yet, the necessity for reliable model systems in the development phase has made research challenging and in vivo models necessary. We have established reliable, reproducible in vitro model systems to evaluate the binding and transport of dopamine-loaded PLGA nanoparticles for the treatment of Parkinson's disease and put the results in context with comparable in vivo results. The in vitro models have provided similar results concerning the usability of the investigated nanoparticles as the previously used in vivo models and thus provide a good alternative in line with the 3R principles in pharmaceutical research.